Efektivitas Metode Fonik terhadap Penurunan Tingkat Keterlambatan Bicara Anak Usia 4-5 Tahun - Soffya Putri; Nadhirotul Laily; Prianggi Amelasasih (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2021)
This research examines the effectiviness of phonic method on reducing the level of speech delay in children aged 4-5 years at Integrated Islamic Kinderganten Al Ummah Gresik. Phonic method is a developed by optimizing all language skills, listening, speaking, writing, and reading. Speech delay occurs when the level of speech development of a child is below the level of quality of speech development of normal children in general according tho their age. This research uses description of quantitative action research type, one group pre-test and post-test design. This research uses a non-probability sampling technique whit a suturated sampling technique. The populations were 10 children and the sample were 6 children in the severe speech delay category and 4 children in the light speech delay category. The data analysis technique used the mann-whitney test analysis. The analysis show that there is an effect of giving phonic method treatment on reducing the level of speech delay in the severe speech delay group. Whereas in the light speech delay group stated that there was no effect of giving phonic method treatment on reducing the level of speech delay. Furthermore, the gain score calculation also shows tha there is no difference in the effectiveness of giving phonic method treatment on reducing the level of speech delay in both the severe speech delay category and the light speech delay category. This suggest tha further researchers provide treatment by experts or people who are experts in their fields, and it is advisable to choose other types of research, such as experimental research, so that the result are more comprehensive.